Ensaios sobre fun????o de produ????o e e ci??ncia: uma abordagem baseada em vine-c??pulas - Oliveira, Michel Angelo Constantino de (2014)
Economic theory uses the production function to develop microeconomic and macroeconomic analyses, respectively at the level of rm and wealth of nations. This thesis proposes a new model for application in the production function, introducing instrumental copulas for modelling the dependence structure of random variables for analysis of asymmetric behavior and extreme events. In the rst test the function of traditional production is modeled using vine-copula for rms from the USA, Germany and England, so it was possible to construct multivariate distributions and estimation of capital-output pairs (y ???? k) variables; work-product (y ???? l); working-capital as a production (k ???? ljy); and know the structures associated dependencies, evaluating the nonlinear dependence and heavy tails. For the second test, following the data and methodological procedures of the rst test, using vine-copula and the construction parameters and coe cient of dependence are the same. The di erence is in the modelling of stochastic frontier and approach insu ciency using this new type of instrument. The marginal distributions were estimated using the gamma function and normal function, several families of copulas were found, including Gumbel, Student-t, BB7, Normal and Clayton which implies changes in behavior and dependence of each pair of variables over the years and in each country, in addition to showing the heavy tails where rms of large and / or small focus. This change in families con rm the stochastic behavior of the data and the production function, in contrast to the inappropriate use of deterministic functions and multivariate normality assumption.